RELATIVE DEPLETION OF NIOBIUM IN SOME ARC MAGMAS AND THE CONTINENTAL CRUST: PARTITIONING OF K, NB, LA AND CE DURING MELT/ROCK REACTION IN THE UPPER MANTLE - Kelemen P.B.; Shimizu N.; Dunn T. (My University, 1993)
Depletion of Nb relative to K and La is characteristic of lavas in subduction-related magmatic arcs, as distinct from mid-ocean ridge basalts. Nb depletion is also characteristic of the continental crust. This and other geochemical similarities between the continental crust and high-Mg# andesite magmas found in arcs suggests that the continental crust may have formed by accretion of andesites. Previous studies have shown that the major element characteristics of high-Mg# andesites may be produced by melt/rock reaction in the upper mantle. In this paper, new data on partitioning of K, Nb, La and Ce between garnet, orthopyroxene and clinopyroxene in mantle xenoliths, and on partitioning of Nb and La between orthopyroxene and liquid, show that garnet and orthopyroxene have Nb crystal/liquid distribution coefficients which are much larger than those of K and La. Similar fractionations of Nb from K and La are expected in spinel and olivine. For this reason, reactions between migrating melt and large masses of mantle peridotite can produce substantial depletion of Nb in derivative liquids. Modeling shows that reaction between ascending, mantle-derived melts and mantle peridotite is a viable mechanism for producing the trace element characteristics of high-Mg# andesite magmas and the continental crust.Alternatively, small-degree melts of metabasalt and/or metasediment in the subducting slab may leave rutile in their residue, and will thus have large Nb depletions relative to K and La [1]. Slab melts are too rich in light rare earth elements and other incompatible elements, and too poor in compatible elements, to be parental to arc magmas. However, ascending slab melts may be modified by reaction with the mantle. Our new data permit modeling of the trace element effects of reaction between small-degree melts of the slab and mantle peridotite. Modeling shows that this type of reaction is also a viable mechanism for producing the trace element characteristics of high-Mg# andesites and the continental crust. These findings, in combination with previous results, suggest that melt/rock reaction in the upper mantle has been an important process in forming the continental crust and mantle lithosphere.